2013
DOI: 10.1007/s13311-013-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds May Open New Routes to Treatment of Amyloid Diseases

Abstract: Protein misfolding disorders, such as Alzheimer's disease and Parkinson's disease, have in common that a protein accumulates in an insoluble form in the affected tissue. The process of aggregation follows a mechanism of seeded polymerization. Although the toxic species is still not well defined, the process, rather than the end product, of fibril formation is likely the main culprit in amyloid toxicity. These findings suggest that therapeutic strategies directed against the protein misfolding cascade should fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 128 publications
0
70
0
Order By: Relevance
“…Because the presence of abnormal Aβ metabolism can be detected 10-20 years before the onset of AD (12,13), early interventions may be possible before widespread and irreversible neurodegeneration has occurred. Although targeting Aβ accumulation has been pursued as a major potential therapeutic strategy against AD (14)(15)(16)(17), no compound selected for this purpose has yet entered clinical use (18,19).…”
mentioning
confidence: 99%
“…Because the presence of abnormal Aβ metabolism can be detected 10-20 years before the onset of AD (12,13), early interventions may be possible before widespread and irreversible neurodegeneration has occurred. Although targeting Aβ accumulation has been pursued as a major potential therapeutic strategy against AD (14)(15)(16)(17), no compound selected for this purpose has yet entered clinical use (18,19).…”
mentioning
confidence: 99%
“…Polyphenols are the most abundant antioxidant compounds present in human diet, and potential beneficial activities in the prevention of degenerative diseases, including amyloidoses, have been attributed to these molecules (20,21). Previous studies provided evidence for the specific interactions of resveratrol (22) and of some flavonoids (23)(24)(25) with the T4 binding sites of TTR and for their ability to stabilize TTR tetramer and to inhibit fibril formation (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Most of the resulting aggregates are highly ordered because they are enriched in crossed β-sheet structures (i.e. amyloid-like polymers) can be stained with dyes such as Congo red or Thioflavin T [99][100][101]. It has been suggested that oligomeric species are the more toxic forms compared to larger aggregates [102].…”
Section: Diseases and Therapy Advancesmentioning
confidence: 99%
“…However, the bioavailability of EGCG and access to the brain is quite poor [99]. The integration of such a compound into NPs to enhance its delivery to the brain is logically studied [78] and appears to inhibit amyloid aggregates in vitro when incorporated to Tet-1 peptide (a neuron-targeting molecule allowing the bypass of the BBB via a retrograde axonal transport) linked selenium NPs [164].…”
Section: Therapeutic Strategies Using Nanoparticles In Ndmentioning
confidence: 99%
See 1 more Smart Citation